Biogenic Amines in Foods - Danquah, A.O.; Benjakul, S.; Simpson, B.K. (Food Biochemistry and Food Processing: Second Edition, 2012)
Biogenic amines (also known as biologically active amines) are low-molecular weight organic compounds produced in biological systems by enzymatic decarboxylation of certain amino acids such as histamine and tyrosine. Examples include dopamine, histamine, norepinephrine, serotonin, and tyramine. They function in the body as neurotransmitters and relay signals between neurons across synapses to impact on mental functions, blood pressure, body temperature, appetite, and several other physiological processes. The levels of biogenic amines in the body are regulated for proper functioning of the various physiological processes that they are associated with. Certain foods contain biogenic amines that can add to the amounts naturally present in the body. High intake of these foods could upset the balance of biogenic amines in the body to cause health problems such as hypotension, hypertension, gastrointestinal distress, headaches and migraine, and others. Thus, it is crucial to curtail the formation and levels of these compounds in certain food products. This chapter discusses the formation and occurrence of biogenic amines in selected food products, their effects of human health and significance to the food industry, their detection, and their fate during processing and storage. The chapter also covers regulation of biogenic amines in foods. © 2012 John Wiley & Sons, Inc..
Keywords: Biogenic amine formation in food products; Biogenic amines in food industry; toxicity; Biogenic amines in foods; Biogenic amines in non-fermented foods; Biogenic amines; aliphatic; aromatic; heterocyclic; Biogenic amines; biologically active amines; Cheese; a fermented food product; Food processing; biogenic amine control; Histamines; capillary permeability; MAO enzyme system; biogenic amines